2010
DOI: 10.1158/0008-5472.can-09-2314
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Inhibits BCL6 Expression in Breast Cancer through a Stat5a-Dependent Mechanism

Abstract: BCL6 is a transcriptional repressor that recognizes DNA target sequences similar to those recognized by signal transducer and activator of transcriptions 5 (Stat5). BCL6 disrupts differentiation of breast epithelia, is downregulated during lactation, and is upregulated in poorly differentiated breast cancer. In contrast, Stat5a mediates prolactin-induced differentiation of mammary epithelia, and loss of Stat5 signaling in human breast cancer is associated with undifferentiated histology and poor prognosis. Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 50 publications
4
86
0
Order By: Relevance
“…It was recently demonstrated independently that STAT5 bound to region B in breast cancer cells (20), which is consistent with our data in both hematopoietic and breast cells. In addition, we have found that these STATs compete for binding to this site, and STAT5 can outcompete STAT3, thereby preventing BCL6 gene expression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was recently demonstrated independently that STAT5 bound to region B in breast cancer cells (20), which is consistent with our data in both hematopoietic and breast cells. In addition, we have found that these STATs compete for binding to this site, and STAT5 can outcompete STAT3, thereby preventing BCL6 gene expression.…”
Section: Discussionsupporting
confidence: 93%
“…BCL6 and STATs also compete to regulate some of the same genes (20,21,26). In liver cells, there are sex-biased genes regulated by STAT5 that affect many cellular processes (22).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, basal activation of STAT5 in healthy human breast epithelia is frequently lost in invasive and metastatic human breast cancer. Indeed, loss of active STAT5 in breast cancer is correlated with poorly differentiated histology and poor prognosis (26). In addition, most human mammary tumors displayed decreased expression of the transcription-related gene ELF1, which was also found downregulated in our study (27).…”
Section: Discussionsupporting
confidence: 72%
“…Peck et al showed that a loss of pSTAT5 from the nucleus predicts for a poor clinical outcome along with the possibility of failure to respond to endocrine therapy in ER+ve breast cancer patients [151]. Interestingly, the expression of Bcl6 is inhibited by prolactin mediated activation of STAT5 in breast cancer [152]. Again, it has been shown that the STAT3 and STAT5 signaling pathway is integrally involved in endocrine resistance and more so in the growth factor-stimulated cases [153].…”
Section: Role In Breast Cancermentioning
confidence: 99%